Pengaruh Lingkungan Kerja Terhadap Produktivitas Kerja Guru Di SMK Se-Kecamatan Ciampe Bogor - Ima Rahmawati; Bella Herlina; Muzhir Ihsan; Hana Lestari (JURNAL KAJIAN ISLAM MODERN, 2022)
The purpose of this study was to determine the effect of the work environment on the work productivity of private vocational high school teachers throughout the Ciampea District, Bogor. This research used quantitative research. The data collected in the form of assumptions analyzed by multiple linear regression analysis. This study uses a non-testing questionnaire. The questionnaire was compiled systematically by the researcher by submitting a written statement, answered by the respondent, and returned to the researcher (Sugiyono, 2018). The questionnaire in this study is a closed questionnaire, which is a questionnaire that contains the answers given by the researcher, so that the respondent can only choose one answer that suits him/herself. The questionnaire in this study contained a series of statements, including five alternative answers, and both positive and negative statements were answered by the teacher. Based on the regression test obtained a significant value of 0.000 <0.05, it can be concluded that there is a positive and significant influence between work productivity and work environment.